Bibliometric Mapping of Trends, Applications and Challenges of Artificial Intelligence in Smart Cities - Shilpi Harnal; Gaurav Sharma; Swati Malik; Gagandeep Kaur; Savita Khurana; Prabhjot Kaur; Sarita Simaiya; Deepak Bagga (EAI Endorsed Transactions on Scalable Information Systems, 2022)
INTRODUCTION: The continued growth of urbanization presents new challenges. This, in turn, will lead to pressure for sustainable environment initiatives, with demands for more and better infrastructure in the diminishing space available and improved quality of life for city dwellers at a more affordable cost. Smart Cities are part of the solution to the growing challenges of urbanization. The adoption of new technologies like artificial intelligence (AI) is transforming cities, making them smarter, faster, and predicting opportunities for improvement.